Pengelolaan Sarana dan Prasarana Pendidikan Sekolah Menengah Pertama - Rahayu, Suri Margi; Sutama, Sutama (Universitas Muhammadiyah Surakarta, 2015)
The aim of the research is to describe the process of procurement, utilization, and maintenance of educational facilities in Junior High School 9 of Surakarta. The type of the research qualitative research with ethnographic design. The place of the reserach in Junior High School 9 Surakarta. The time of the research Â is started from Â May to December 2015. The research subjects are, teachers, business Infrastructure, and students. Technique in collecting the data was by interviews, observation, and documentation. Validity of the data with source triangulation, triangulation techniques, triangulation time. The interview process with the first order and second order understanding understanding. Data analysis of techniques with methods groove. Results of the study are (1) The procurement process facilities and infrastructure that is done with consultation with a team of schools developers, adjusted for allocation and priority program activities school (2) Utilization of facilities and infrastructure that many students who misuse the facilities and infrastructure available, although the utilization not optimal, but it has been used by the entire school community, and (3) treatment facilities and infrastructure that is conducted periodically based on reporting from the management of facilities and infrastructure, and by all study groups as well as having a special service officer for the division of a particular area.